Manajemen Sumber Daya Manusia Guru Dalam Meningkatkan Kreativitas Pembelajaran di Sekolah Dasar Negeri 3 Tirtanadi - Sahabudin Sahabudin; Ziadatul Khair; Elita Nurianti (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2025)
The formulation of the problem in the research is: how is the creativity of teachers' human resources (HR) and the application of creativity in the learning system at SDN 3 Tirtanadi? This research aims to determine creativity and application in the learning system at SDN 3 Tirtanadi. The type of research used is descriptive qualitative with observation, interview and documentation techniques. Data analysis techniques use data reduction, data presentation, data verification and triangulation. The results of the research show that teachers who teach at SDN 3 Tirtanadi are generally able to make and carry out: Learning planning, managing the implementation of teaching well and carrying out teaching assessments well and pareasily. Then the application of creativity carried out by teachers in carrying out the learning process at SDN 3 Tirtanadi is; carrying out workshops/teacher training internally at schools, activating teachers in implementing MGMP, carrying out visits/comparative studies to other schools, increasing the availability of facilities, in the form of; learning media, curriculum tools and other necessary teaching aids, and increasing good cooperation between all components or educational stakeholders.